Description and phylogenetic relationships of a new species of treefrog of the Dendropsophus leucophyllatus group (Anura: Hylidae) from the Amazon basin of Colombia and with an exceptional color pattern - Rivera-Correa, Mauricio; Orrico, Victor G. D. [UNESP] (Magnolia Press, 2013)
We describe Dendropsophus manonegra sp. nov. from the upper Amazon basin in the eastern foothills of the Andes in Colombia (1° 47' 42.2 N, 75° 38' 48.7 W; 1040 m a.s.l.). Phylogenetic analysis of DNA sequences of 2582 aligned base pairs of the 12S and 16S rRNA genes recovered the new species as a member of the D. leucophyllatus species group and sister to D. bifurcus. Morphological traits, such as the presence of pectoral glands in males and females, support this hypothesis. The new species is readily distinguished from all other members of the species group by having bluish-black coloration on fingers, toes, webbing, axillary membranes, groin and hidden surfaces of arms and legs. Some aspects on the composition and systematics of the D. leucophyllatus group are discussed. © 2013 Magnolia Press.
Keywords: Amazonia; Amphibia; Morphology; Species description; Taxonomy